Experimental study of synthetic osteoplastic material easygraft® (Sunstar GUIDOR®) hardening due to different methods of its preparation - Kostenko, Y.; Mochalov, Y. (Actual Dentistry, 2018)
Resume. Usage of osteoplastic materials for primary and secondary defects in jawbone eliminating is a daily practice for most dental clinics in the world. Due to clinical opinions synthetic materials, including composites ones and with the presence of a polymer component in the composition have a good perspective in future. They have osteoconductive properties and the use of such materials involves less risk than materials of natural origin. According to fact that clinicians have questions about the risk of early hardening of easygraft® CLASSIC and easygraft® CRYSTAL during long-lasting manipulations (filling large defects in bone, sinus-lifts etc.) and absence of specific instructions by manufacturer about exposure time of the material in N-methyl-2-pyrrolidone solution (BioLinker®), a series of experiments was performed to study the duration of easygraft® Sunstar GUIDOR plasticity period depending on the exposure time in the BioLinker® solution in two versions of bone wounds models (chicken egg white with saline solution and chicken liver homogenate with saline solution). The number of demonstration samples of easygraft® was 12, the exposure variants of the material in the BioLinker® were 20 seconds, 40 seconds, 1 minute, 5 minutes, 10 minutes, 20 minutes. The mechanical properties of the material in the wound model were verified manually using metal dental curved tweezers. Results. The period of plasticity of easygraft® material placed in the egg white bone wound model ranged from 46 seconds to 8 minutes 5 seconds; almost direct proportional dependence of the duration on exposure period of the material in the BioLinker® was observed. Regarding the second bone wound model (with a homogenized chicken liver) the material began to harden approximately on the 10th second after application and the plasticity period was from 4 seconds to 2 minutes 40 seconds. At the same time, there was no linear dependence on the time of exposure in the BioLinker®. The material exposed in BioLinker® for 5 minutes and longer hardened in the wound model in the period from 2 minutes and 35 seconds to 2 minutes 50 seconds after placing in the wet conditions. Conclusions. The obtained results may be the reason for improving the clinical guidelines for the use of easygraft® materials Sunstar GUIDOR® in the clinic for the elimination of large-volume bone defects and the operation of a sinus lift. In such cases, the material should be prepared (mixed with BioLinker®) «ex tempore» – 5 to 10 minutes before entering the bone wound. Key words: bone, plastic, β-tricalcium phosphate, easygraft, exposure.